Gravimetric characterization of solid waste from selective collection in the city of Rio de Janeiro in 2019 - Quintaes, Bianca Ramalho; Conde, André Luiz Ferreira Menescal; Cordeiro, Sérgio de Oliveira; Garcez, Júlio César; Campos, Juacyara Carbonelli (Seven Editora, 2023)
This research describes the types of plastic packaging consumed in Rio de Janeiro, through the selective collection of recyclables carried out by the Municipal Company of Urban Cleaning of the City of Rio de Janeiro (COMLURB). The quantities, types and manufacturing companies of the products contained in the packages in the neighborhoods of different Planning Area (PA) were surveyed. The residues were characterized according to their physical composition: paper, plastic, glass and metal. The Society of Plastics Industries (SPI) Classification was the parameter for classifying plastic materials. A total of 18 samples of plastic waste were analysed. The results point to higher mass percentages for the paper component, 39.82%; plastic, 28.89%; glass, 25.84% and metal 5.45%. It was observed that 27% of the plastics are Polyethylene Terephthalate (PET) Crystal and 1.71% are PET Waste (no known technology for recycling); Polyethylene (PE) film plastics are 4.23%. The research identified 503 brands and 3,525 products of these brands, including cleaning packaging, personal hygiene, and food. The brands Nestlé, Unilever, Coca Cola, Danone, Bombril, Arcor were observed with the highest rates of consumption of plastic packaging by the population. DOI:https://doi.org/10.56238/alookdevelopv1-026